Implementation of The Australian Sports Search Method in Fencing Sports Branches for Junior High School Students - Muh. Thoif Al Fattah; Jamaluddin; Amahoru, Nurul Musfira (Universitas PGRI Palembang, 2025)
This study aims to evaluate the effectiveness of the Australian Sports Search method in detecting fencing sport talent among junior high school students in Polewali Mandar Regency, specifically at SMPN 2 Polewali and SMPN 4 Polewali. This method integrates anthropometric measurements and physical condition tests as tools to assess students' potential talent in fencing. This research uses a quantitative method with a mixed approach with a sequential explanatory design, which combines quantitative and qualitative analyses. Quantitative data were obtained through anthropometric measurements including height, weight, sitting height, and arm span, and physical condition tests including eye-hand coordination, agility, leg and arm muscle explosiveness, speed, and aerobic endurance. Qualitative data was obtained through interviews and observations of students and coaches to understand the factors influencing the measurement and test results. The results showed that the Australian Sports Search method was effective in identifying students with potential fencing talent, with 11 students or 23,26% showing potential results. This study also found that this method is effectively implemented to identify students' potential fencing talent